Safe Schools Safe Communities: A Directory of Resources for Pennsylvania. - Pennsylvania State Dept. of Education, Harrisburg; Pennsylvania State Dept. of Education, Harrisburg ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This document contains a directory of resources available in Pennsylvania to help achieve the goal of safe schools. Following a copy of the Safe Schools Act of 1993, nine sections list agencies that provide services and products under the headings of: conflict resolution/mediation, gangs, suicide, crisis response, family violence, diversity, school policy, community collaborations, and training resources. Resources include printed materials (e.g., books, curricula, newsletters, manuals), videos, and training programs. A title index to resources is provided. Appendixes include directories of Pennsylvania county and regional agencies concerned with domestic violence, children and youth services, and school-based probation programs. (LMI)
Availability: Project Success, Center for Schools and Communities, 27 Miller Street, Lemoyne, PA 17043.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Cooperation; Conflict Resolution; Cultural Awareness; Elementary Secondary Education; Family Violence; Juvenile Gangs; Multicultural Education; Partnerships in Education; School Policy; School Safety; School Security; Suicide; Violence; Pennsylvania; Reference Materials, Directories/Catalogs.